LOCAL WISDOM OF KAMPUNG NAGA IN MITIGATING DISASTER AND ITS POTENCIES FOR EDUCATION TOURISM DESTINATION - Enok Maryani; Ahmad Yani (ASEAN Journal on Hospitality and Tourism, 2015)
Indonesia is a multi-islands, multi-ethnics and multi-disasters country. Each etnic has a set of culture which is adapted into its environment, including in anticipating the pontential disaster around its area. The culture which is transmited or inherited from one generation to the next, has been proved its superiority, known as local wisdom. Local wisdom, in the form of life philosophy, attitude, and behavior guidance, will help the society to survive from various threats that distrupt their existance from natural disaster and life dynamics. Sundanese people, particularly in Kampung Naga Tasikmalaya, has a local wisdom which can protect their enviroment. This is very important in mitigating  disaster, such as landslide, drought, and polution. This society has been realized that disater will occured if their ennvironment is damaged. Local wisdom in disaster mitigation can be seen in the form of architecture, landuse zoning, land management for sustainable enviroment. This value of local wisdom is very important to be transmited and transformed to both domestic and international tourist through ecotourism. Ecotourism is known as sustainable tourism, green tourism, and edutourism because it has the vision of enviromental sustainable, activity without pollution, conservation, society empowerment, and appreciation for nature and society culture. The shift of tourism paradigm (from travel package and mass tourism to individual and small scale; from psikosentris to alosentris; from  foreign investment to own  society; and from European stypes to the natives) become a potential for Kampung Naga to be an ecotourism destination which has educational tourism. Besides, the potencies of Kampung Naga to be tourism destination also can be seen from strategic access from Bandung-Tasikmalaya-Pangandaran; openess in accepting the tourist; beautiful nature, various souvenirs, and tracking. Moreover, the approciation for Kampung Naga's society in preserving their enviroment and mitigating disaster become the other visions of making Kampung Naga as education tourism destination